2019
DOI: 10.12965/jer.1938688.344
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aquatic exercise program on low-back pain disability in obese women

Abstract: Low-back pain (LBP) is one of the most current causes to reduce work performance, limit daily activities and raising health cost, and it is increasing as obesity growing as a public health concern. While obese LBP people cannot avoid weight load on the spine in any exercise, they can easily carry out exercise in water. This study aimed to investigate the effect of aquatic exercise on LBP disability among obese women. In this study, a total of 39 women with body mass index (BMI)≥ 27 kg/m 2 who suffering from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“… 70 , 77 Obesity measures, especially anthropometrical measurements, eg, BMI and WHR, have been repeatedly associated with LBP. 78 However, these associations have been questioned, 79 and lack detailed investigations, 80 in particular for ECW levels. Our univariate multiple regression analysis showed that both WHR, and ECW adjusted for age and sex, were significantly associated with LBP-disability scores.…”
Section: Discussionmentioning
confidence: 99%
“… 70 , 77 Obesity measures, especially anthropometrical measurements, eg, BMI and WHR, have been repeatedly associated with LBP. 78 However, these associations have been questioned, 79 and lack detailed investigations, 80 in particular for ECW levels. Our univariate multiple regression analysis showed that both WHR, and ECW adjusted for age and sex, were significantly associated with LBP-disability scores.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of general pain and disability were the 2 variables examined by approximately all the studies with the use of visual analogue scale [19-21, 24, 30, 34], Quebec Back Pain disability Scale (QBPdS) [30], oswestry disability Questionnaire [18,19,25,35], Roland Morris disability Questionnaire [20][21][22], and Short Form-12/36 [20-22, 25, 26, 35], which assesses the quality of life and general health of the tested subjects. According to the high methodological quality study by Pires et al [30], general body pain was reduced by applying exercise in water.…”
Section: Discussionmentioning
confidence: 99%
“…Pain intensity, disability, and quality of life were variables examined in LBP patients with the use of different scales, such as visual analogue scale, the oswestry disability Questionnaire, the Roland Morris disability Questionnaire, or Short Form-36/12 [18][19][20][21][22]. Also, the functional and psychological state of LBP patients were investigated with a number of assessment tools [18,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AE routine included walking (forward and backward), knee flexion and extension (in standing position), side lunges, jogging, side stepping, standing knee lift, hip kicker, leg balance (right & left), deep water cycling (using woggle), pool plank and wall push up [19][20][21]. The intensity and frequency of the exercise gradually increased every week, with an intensity of 13 -International Journal of Human Movement and Sports Sciences 10(4A): 1-9, 2022 3 17 Borg-Scale (60-70%) of the participant's maximum heart rate [22]. An overview of the AE program is detailed in Table 1.…”
Section: Aquatic Exercise (Ae)mentioning
confidence: 99%